Physiology of elite young male athletes - Armstrong, N.; McManus, A. M. (The Elite young athlete, 2011)
Performance in sport takes place within a matrix of bio-cultural characteristics but boys` success in elite youth sport is underpinned by a range of age-and maturity-related physical and physiological variables which act in a sport-specific manner to influence performance. Stature, body mass, and muscle mass increase with growth and maturation and earlier maturing boys are generally taller, heavier, and more muscular than boys of the same chronological age who mature later. Earlier maturing boys also benefit from changes in body shape which are advantageous in many sports. Marked increases in muscle strength and muscle power are expressed during adolescence. The muscle enzyme profile needed to promote the anaerobic generation of energy is enhanced as children move through adolescence into young adulthood. Aerobic fitness benefits from age and/or maturation-related increases in stroke volume, haemoglobin concentration, and muscle mass. These individual differences are most pronounced at 12-15 years when participation in elite youth sport is at its peak. Many boys fulfil their potential, gain great pleasure from elite youth sport and become elite adult sportsmen. Other equally talented boys are denied access to elite youth sport through selection policies which are influenced by stage of maturation or age relative to the beginning of the selection year. Others drop-out prematurely through early specialisation in a sport inappropriate for their late adolescent or adult physique. Boys are not mini-men and coaches and parents should focus on providing opportunities for all boys and on nurturing talent irrespective of the ticking of individual biological clocks.